2021
DOI: 10.1016/j.ypmed.2021.106643
|View full text |Cite
|
Sign up to set email alerts
|

The national FIT-based colorectal cancer screening program in the Netherlands during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has affected many healthcare services worldwide. Like many other nations, the Netherlands experienced large numbers of individuals affected by COVID-19 in 2020, leading to increased demands on hospitals and intensive care units. The Dutch Ministry of Health decided to suspend the Dutch biennial fecal immunochemical test (FIT) based colorectal cancer (CRC) screening program from March 16, 2020. FIT invitations were resumed on June 3. In this study, we describe the short-term effects of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…A decrease in DC compliance was also observed in other CRC screening programs [16][17][18]. Corely et al (2017) demonstrated that a DC after 10 months was associated with a higher CRC risk and more advanced-stage CRC compared to a DC at 8-30 days [4].…”
Section: Discussionmentioning
confidence: 84%
“…A decrease in DC compliance was also observed in other CRC screening programs [16][17][18]. Corely et al (2017) demonstrated that a DC after 10 months was associated with a higher CRC risk and more advanced-stage CRC compared to a DC at 8-30 days [4].…”
Section: Discussionmentioning
confidence: 84%
“…This included a change from non-fixed to fixed appointment time slots 33. The national breast and CRC screening programmes in the Netherlands were suspended on 16 March 2020 and invitations for screening were gradually restarted beginning in May 2020 6 40 42. In Australia, the pandemic has not widely affected kit distribution which is mailed to participants 19.…”
Section: Discussionmentioning
confidence: 99%
“…Many CRC screening organisations have successfully limited the impact of the pandemic on CRC burden by expeditiously resuming screening services after the disruption. 22 , 23 However, note that the predicted impact still amounts to 339-987 excess CRC-related deaths in each country simulated. As many countries all over the world have faced a disruption to CRC screening programmes 1 , globally a considerable number of potentially excess CRC-related deaths can be expected if countries lack colonoscopy capacity to overcome the screening backlog.…”
Section: Discussionmentioning
confidence: 99%
“…FIT participation rates and compliance to diagnostic follow-up in the recovery period were set equal to pre-pandemic levels. 22 , 23 We assumed that the order in which individuals were screened during the recovery period was based on the original date of invitation. On average, individuals were delayed for primary screening by 1.5 months ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%